Vitalizing of the Religious Sciences - Calverley, Edwin E. (The Muslim world, 1924)
This article is a careful but greatly condensed analysis of the Book of the Worship (Kitab as-Sala), the Fourth Book of the First Quarter of al-Ghazzali's Ihya Ulum al-Din. Dr. Calverley's complete Translation of this Book, with Introduction and Commentary from original sources, is expected to appear this year.